2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6186033
|View full text |Cite
|
Sign up to set email alerts
|

Performance of multi-junction silicon-based thin film solar cells under concentrated sunlight

Abstract: Multi-junction silicon-based thin-film concentrator solar cells are promising candidate to achieve both low-cost and high-efficiency. For the application of silicon-based thin film solar cells to concentrator photovoltaics, it is required to be revealed the light intensity dependence of the performance of silicon-based thin film solar cells. From these reasons, in this study both calculation and experimental studies were conducted with several types of single-junction and multi-junction tandem solar cells. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Kasashima et al used a heterojunction microcrystalline silicon (μc-Si:H) thin film cell which was made by plasma enhanced chemical vapor deposition (PECVD) for concentration, they deposited wide bandgap microcrystalline silicon oxide (μc-Si 1 À x O x :H) film as the top P-type layer to decrease the recombination of carriers, the efficiency of the cell reached 10.4% under 11.8 suns [98]. They also used two-junction and three-junction cells made of a-Si:H and μc-Si:H films for concentration, the current mismatch between the sub-cells increased with concentration ratio, the two-junction cell had the highest efficiency of 12.2% under 2.7 suns [99]. They also did numerical analysis to above cells using the AMPS-1D (Analysis of Microelectronic and Photonic Structures) software and found that the efficiencies of single-junction and three-junction cells could reach 13% and 23% under 50 suns after optimization [98,99].…”
Section: Silicon-based Hetero-junction and Thin Film Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kasashima et al used a heterojunction microcrystalline silicon (μc-Si:H) thin film cell which was made by plasma enhanced chemical vapor deposition (PECVD) for concentration, they deposited wide bandgap microcrystalline silicon oxide (μc-Si 1 À x O x :H) film as the top P-type layer to decrease the recombination of carriers, the efficiency of the cell reached 10.4% under 11.8 suns [98]. They also used two-junction and three-junction cells made of a-Si:H and μc-Si:H films for concentration, the current mismatch between the sub-cells increased with concentration ratio, the two-junction cell had the highest efficiency of 12.2% under 2.7 suns [99]. They also did numerical analysis to above cells using the AMPS-1D (Analysis of Microelectronic and Photonic Structures) software and found that the efficiencies of single-junction and three-junction cells could reach 13% and 23% under 50 suns after optimization [98,99].…”
Section: Silicon-based Hetero-junction and Thin Film Cellsmentioning
confidence: 99%
“…They also used two-junction and three-junction cells made of a-Si:H and μc-Si:H films for concentration, the current mismatch between the sub-cells increased with concentration ratio, the two-junction cell had the highest efficiency of 12.2% under 2.7 suns [99]. They also did numerical analysis to above cells using the AMPS-1D (Analysis of Microelectronic and Photonic Structures) software and found that the efficiencies of single-junction and three-junction cells could reach 13% and 23% under 50 suns after optimization [98,99]. However, the light-induced recession of the thin film cells will be more serious under concentration, the fill factor and efficiency of the cell decreased quickly with the increase of illumination time under 10 suns [100].…”
Section: Silicon-based Hetero-junction and Thin Film Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a static device position, which results in a reduced illumination intensity, , the decrease of J SC can be related to the decreased amount of photons absorbed by the photovoltaic device. On the other hand, changes in V OC are directly related to the splitting of the quasi-Fermi level under illumination. , Here, we observed that a slight improvement in fill factor (FF) values upon changes in the angle between 0 and 60° has an analogous origin to the effects of the decreased photon flux on the solar cell performance. , These effects are usually related to the distribution of the field in the solar cell upon illumination and a lower recombination rate of electron–hole pairs in the active layer of the solar cell. , Note that here an improvement in the built-in field brings no positive effect on V OC , which is dictated by the reduced number of the photogenerated electron–hole pairs and consequently reduced quasi-Fermi level splitting with an increasing angle.…”
Section: Results and Discussionmentioning
confidence: 71%
“…For the FF , no clear trend is observed for the temperatures investigated. For temperatures below 40 °C, the fill factor decreases with increasing intensity; while for higher temperatures the fill factor increases with an increasing intensity, suggesting a tradeoff between several competing mechanisms (such as possible changes in recombination and/or field distribution profiles in the sub cells), influencing FF over temperature and intensity range. The resulting efficiency η shows an increase with increasing intensity, but a decrease with increasing temperature …”
Section: Resultsmentioning
confidence: 99%